Novel Inhibitors of Toxin HipA Reduce Multidrug Tolerant Persisters - Li, Tongqing (ACS Med Chem Lett, 2016)
[Image: see text] Persisters are a small fraction of drug-tolerant bacteria without any genotype variations. Their existence in many life-threatening infectious diseases presents a major challenge to antibiotic therapy. Persistence is highly related to toxin–antitoxin modules. HipA (high persistence A) was the first toxin found to contribute to Escherichia coli persistence. In this study, we used structure-based virtual screening for HipA inhibitors discovery and identified several novel inhibitors of HipA that remarkably reduced E. coli persistence. The most potent one decreased the persister fraction by more than five-fold with an in vitroK(D) of 270 ± 90 nM and an ex vivo EC(50) of 46 ± 2 and 28 ± 1 μM for ampicillin and kanamycin screening, respectively. These findings demonstrated that inhibition of toxin can reduce bacterial persistence independent of the antibiotics used and provided a framework for persistence treatment by interfering with the toxin–antitoxin modules.